A 2D and 3D electrical impedance tomography imaging using experimental data - Shulga, Dmitry (Видавництво Львівської політехніки, 2012)
In this paper model, method and results of 2D and 3D conductivity distribution imaging using experimental data are described. The 16-electrodes prototype of computer tomography system, special Matlab and Java software were used to perform imaging procedure. The developed system can be used for experimental conductivity distribution imaging and further research work.
Keywords: Electrical Impedance Tomography; Finite Element Method; inverse problem; regularization